The U.S. coal sector between shale gas and renewables: Last resort coal exports? - Christian Hauenstein; Franziska Holz (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Coal consumption and production have sharply declined in recent years in the U.S., despite political support. Reasons are mostly unfavorable economic conditions for coal, including competition from natural gas and renewables in the power sector, as well as an aging coal- fired power plant fleet. The U.S. Energy Information Administration as well as most models of North American energy markets depict continuously high shares of coal-fired power generation over the next decades in their current policies scenarios. We contrast their results with coal sector modelling based on bottom-up data and recent market trends. We project considerably lower near-term coal use for power generation in the U.S. This has significant effects on coal production and mining employment. Allowing new export terminals along the U.S. West Coast could ease cuts in U.S. production. Yet, exports are a highly uncertain strategy because the U.S. could be strongly affected by changes in global demand, for example from non-U.S. climate policy. Furthermore, coal production within the U.S. is likely to experience regional shifts, affecting location and number of mining jobs.
Keywords: Q02; Q38; Q47; L72; C61; 330; USA; coal; international coal trade; EMF34; numerical modeling; scenarios